Usaha Kepala Sekolah dalam Meningkatkan Proses Pembelajaran Al-Qur’an di SMK Ma’arif 1 Sleman Yogyakarta - Mulyadi, Taufik Arif (Medan Resource Center, 2022)
The purpose of this research is to understand the implementation of Qur'an learning at SMK Ma'arif 1 Sleman, to identify the efforts of the principal in enhancing the Qur'an learning process at SMK Ma'arif 1 Sleman, and to determine the supporting and inhibiting factors faced by the principal in improving the Qur'an learning process at SMK Ma'arif 1 Sleman. This research is a qualitative study set at SMK Ma'arif 1 Sleman. Data collection was carried out using observation, interviews, tests, and documentation. The research results indicate that: (1) The implementation of Qur'an learning at SMK Ma'arif 1 Sleman is quite good, while the students' ability to read the Qur'an falls into the adequate category. (2) Students face difficulties in memorizing hijaiyyah letters, understanding tajweed rules, waqf signs, mad reading laws, and the application of makhraj letters. (3) The efforts made by the principal to enhance the Qur'an learning process at SMK Ma'arif 1 Sleman include providing guidance to students to continually learn to read the Qur'an and giving teachers the freedom to conduct Qur'an learning in the classroom, among others. (4) The supporting factors for the principal's efforts are the availability of learning facilities and support from teachers, among others.